Recovery from shift work - Kalkanis, Alexandros; Demolder, Saartje; Papadopoulos, Dimitrios; Testelmans, Dries; Buyse, Bertien (Frontiers in Neurology, 2023)
One fifth of today's workforce is engaged in shift work and exposed to various mental and physical health risks including shift work disorder. Efficiently recovering from shift work through physical and mental interventions allows us to mitigate negative effects on health, enables a better work-life balance and enhances our overall wellbeing. The aim of this review is to provide a state-of-the-art overview of the available literature. The role of sleep timing and naps, light therapy and psychotherapy, diet and exercise in recovery from shift work is presented here. We further review the impact of shift schedules and social support on post-shift unwinding.